Private firms' financial constraints and share pledging by controlling shareholders of publicly listed firms: Evidence from China - Guo, Kai; Ke, Bin; Tang, Song (Journal of Corporate Finance, 2023)
Private firms face significant financial constraints that limit their investment and growth. Recognizing the fact that many private firms belong to business groups that contain at least one publicly listed firm, we hypothesize that private firms can partially relieve their financial constraints through the cash proceeds from share pledging of publicly listed firms by the common controlling shareholder. Using data from publicly listed Chinese firms, we find results consistent with this hypothesis, especially for private firms facing greater financial constraints. However, such share pledging also creates a negative spillover on shareholder value of publicly listed firms under common ownership.